THE USE OF POWTOON SOFTWARE PROGRAM IN TEACHING AND LEARNING PROCESS: THE STUDENTS' PERCEPTION AND CHALLENGES - Entis Sutisna; Lungguh Halira Vonti; Septian Agung Tresnady (UNIVERSITAS PAKUAN, 2019)
This research aimed to find out the students perception and challenges in lteaching and learning process through Pow Toon software. Qualitative data are gained from classroom observation, questionnaire, and interview. The qualitative data are analysed by assembling the data, coding the data, comparing the data to the theory, building interpretations, and reporting the outcomes. The result of the research shows the students' perceptions of learning through this kind of software and describes the challenges found by both the teachers and the students. Thus, it is also found out that learning by using animation video also make a learning process more interesting. However, one of the challenges that the students found in learning through the animation video from Pow Toon software is the motion of the animation itself that distract students concentration; therefore, the teachers who will use the media should consider best instructional technique in the teaching and learning process. In addition, the duration when the explanation on the video is too fast. So they need to extra concentrate to the material itself. Yet, the use of digital media in teaching and learning process is one of innovative ways and it is a necessity for the millenium era.